Crosstalk Between Autophagy and the cGAS–STING Signaling Pathway in Type I Interferon Production - Zhang, Kunli; Wang, Sutian; Gou, Hongchao; Zhang, Jianfeng; Li, Chunling (Frontiers in Cell and Developmental Biology, 2021)
Innate immunity is the front-line defense against infectious microbes including viruses and bacteria. Type I interferons (IFNs) are pleiotropic cytokines that perform antiviral, antiproliferative, and immunomodulatory functions in cells. The cGAS-STING pathway comprised with the main DNA sensor cyclic guanosine monophosphate-adenosine monophosphate synthase (cGAS) and stimulator of interferon genes (STING), is a major pathway mediates immune reaction and is involved in a strong induction of type I IFNs production which can fight against microbial infections. Autophagy is an evolutionarily conserved degradation process that is required to maintain host health and facilitate the capture and clearance of invading pathogens by the immune system. Mounting evidences have indicated that autophagy plays an important role in the signaling pathway of cGAS-STING mediated type I IFNs production. This review briefly summarizes the research progress of autophagy regulates cGAS-STING pathway in type I IFN production, with a particular focus on the crosstalk between autophagy and cGAS-STING signaling during pathogenic microorganism infection.